Factors Affecting Low Birth Weight Incidence at Cipto Mangunkusumo Hospital, Jakarta - Rachma F. Boedjang; Rinawati Rohsiswatmo; Titi S Sularyo; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 1998)
A case-control study was conducted during the period of April-July 1997 to determine factors affecting the incidence of low birth weight infants born at Cipto Mangunkusumo Hospital, Jakarta. Of the 300 singleton infants (150 LBW and 150 non-LBW) studied, five risk factors were determined: (1) maternal education (p = 0,027), (2) maternal weight gain during pregnancy (p < 0,001), (3) interval between regnancy intervals (p = 0,041), (4) history of previous LBW (p = 0,004), and (5) maternal health condition during pregnancy (p < 0,0001). The mean anthropometric measurements of male non-LBW were significantly greater than female non-LBW infants.